Chemical Composition, Cytotoxic and Antibacterial Activities of Essential Oils of Cultivated Clones of Juniperus communis and Wild Juniperus Species. Issue 9 (16th August 2018) - Maurya, Antim K.; Devi, Renuka; Kumar, Ashish; Koundal, Rajkesh; Thakur, Soni; Sharma, Anamika; Kumar, Dharmesh; Kumar, Rakshak; Padwad, Yogendra S.; Chand, Gopi; Singh, Bikram; Agnihotri, Vijai K.
Abstract : Needles of seven cultivated clones (C1 – C7) of Juniperus communis at lower altitude and three wild Juniperus species ( J .  communis, J .  recurva and J .  indica ) at higher altitudes were investigated comparatively for their essential oils (EOs) yields, chemical composition, cytotoxic and antibacterial activities. The EOs yields varied from 0.26 to 0.56% (v/w) among samples. Sixty‐one volatile components were identified by gas chromatography‐mass spectrometry (GC/MS) and quantified using gas chromatography GC (FID) representing 82.5 – 95.7% of the total oil. Monoterpene hydrocarbons (49.1 – 82.8%) dominated in all samples ( α ‐pinene, limonene and sabinene as major components). Principal component analysis (PCA) of GC data revealed that wild and cultivated Juniperus species are highly distinct due to variation in chemical composition. J .  communis (wild species) displayed cytotoxicity against SiHa (human cervical cancer), A549 (human lung carcinoma) and A431 (human skin carcinoma) cells (66.4 ± 2.2%, 74.4 ± 1.4% and 57.4 ± 4.0%), respectively, at 200 μg/ml. EOs exhibited better antibacterial activity against Gram‐positive bacteria than against Gram‐negative bacteria with the highest zone of inhibition against Staphylococcus aureus MTCC 96 (19.2 ± 0.7) by clone‐7. As per the conclusion of the findings, EOs of clone‐2, clone‐5 and clone‐7 can be suggested to the growers of lower altitude, as there is more possibility of uses of these EOs in food and medicinal preparations. Abstract :